Perubahan Tingkat Pengetahuan, Asupan Zat Gizi dan Tekanan Darah Berdasarkan Edukasi Gizi pada Penderita Hipertensi di UPTD Puskesmas Gianyar I - Hariani, Sri Ayu; Nursanyoto, Hertog; Puryana, I Gusti Putu Sudita (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
One of the non-communicable diseases (NCDs), which is the most serious health problem today, is hypertension. Hypertension is a condition where the systolic pressure is ≥ 140 mmHg and/or diastolic ≥ 90 mmHg. The aim of this research is to determine changes in the level of knowledge, nutritional intake and blood pressure based on nutritional education for hypertension sufferers at the Gianyar I Health Center. This research method is The quasi-experiment was carried out in March – June 2024 at the Gianyar I Community Health Center involving 30 intervention group samples and 30 control group samples. The population of this study were hypertensive patients who took part in educational class activities at the UPTD Gianyar I Health Center. The sample was taken using a purposive sampling technique. Inclusion criteria are: age ≥ 18 years, patients who have received hypertension therapy for at least 1 month (old patients) and are willing to be interviewed and become samples and sign a research consent form, while the exclusion criteria are hypertension sufferers who experience complications that cause the research process to be disrupted, are absent, suffer from disorders. souls, and pregnant and breastfeeding mothers. Statistical tests used the Mann Whitney and Wilcoxon tests. The average level of knowledge increased from 57.90 to 79.66 after education, the sample's nutritional intake after education became good at 29 (96.7%) and the sample's average systolic blood pressure was 156.7 mmHg to 140.5 mmHg and diastolic blood pressure. 89.8 mmHg to 82.8 mmHg. The results of statistical tests showed that there were differences in levels of knowledge, nutritional intake, and blood pressure (p 0.05). Community health centers should provide and program nutritional education activities in the form of counseling for certain disease groups, especially the hypertension group.